Perfil químico de extrativos de Eucalyptus spp. e sua bioatividade sobre Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae) - Batista, Bibiana Fontana (2024)
Plant extracts, such as essential oils (EOs), are a complex mixture of heterogeneous, volatile, and liquid chemicals involved in plant defense functions, such as feeding inhibitors. Species of the genus Eucalyptus are potential producers of extracts. Among the substances in species of this genus, eucalyptol, p-cymene, α-pinene, and β-pinene stand out, which are related to different biological processes. Phenolic compounds have defense functions against herbivory, oxidative stress, protecting plants, and acting as adjuvants in reproductive processes. The study aimed to evaluate the potential of extracts obtained from leaves of Eucalyptus benthamii and E. saligna for the control of the eucalyptus bronze bug (Thaumastocoris peregrinus). Leaves of the species Eucalyptus benthamii and E. saligna were first collected in the municipality of São Sepé, RS, in February 2021, and the second collection was in February 2022, in the municipality of Cachoeira do Sul, RS. EOs were obtained by hydrodistillation using a Clevenger-type apparatus for 3 hours in triplicate, and yields were calculated relative to the fresh weight of plant material extracted from the leaves (% w/w). Ethanolic extracts (EEs) were also obtained from the leaves by hot extraction using a Soxhlet apparatus in triplicate. The toxicity of the EOs at concentrations of 0.5%, 1%, 1.5%, and 2%, and 0.5%, 1%, 1.5%, 2%, and 4% of the crude EEs of the species E. saligna on T. peregrinus was tested. Their effects were related to the chemical composition of the extracts analyzed by GC-MS and UPLC, respectively. The yields of the EOs from the first collection for E. benthamii were 1.0% and for E. saligna were 0.18%. For the EOs obtained from plant material from the second collection, conducted in Cachoeira do Sul, extractive yield for E. benthamii was 1.38% and for E. saligna was 0.31%. Through the study, we identified in the EOs for E. saligna among the major substances α-pinene, eucalyptol, α-terpinol, limonene, and spatulenol, and for E. benthamii, α-pinene, aromadendrene, and valencene. It was possible to verify that the difference between the two species lies in the presence of eucalyptol in the EOs of E. saligna, demonstrating that the species have different chemical compositions. For the ethanolic extracts, from the first collection site, we observed an extractive yield of 23.06% for E. saligna and 21.75% for E. benthamii, and for the second collection site, a yield of 19.27% and 15.63% for the extract. The EEs present specific chemical characteristics depending on the species. For E. saligna, phenolic compounds, saponins, and hydrolyzable tannins were detected. For E. benthamii, a different class of tannins (condensed) was detected, reinforcing the individuality of the extracts of each species. The EO of E. saligna at the highest tested concentration (2%) caused 100% mortality of T. peregrinus specimens after 48 hours, and at the lowest concentration (0.5%), it suppressed about 46%. The plant extracts from E. saligna have potential for use in controlling Thaumastocoris peregrinus. EOs show activity relative to insect survival, while EEs show activities related to feeding inhibition.